Tanzania: From mining to oil and gas - Alan Roe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper compares and contrasts the economic situation in Tanzania during the resurgence of gold and diamond production after 1999, with the situation that is now emerging as the country begins to exploit very large resources of natural gas mainly from the Indian Ocean. The mining boom after 1999, provided the authorities with significant lessons and opportunities associated with managing natural resources wealth. The paper assesses some of the key component issues and interprets these in the context of the new possibilities (and dangers) opened up by the natural gas revolution.
Keywords: 330; Tanzania; gas; liquefied natural gas; mining; energy generation